2013
DOI: 10.1111/imm.12082
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of natural killer cell activating receptors in blood versus bone marrow in patients with monoclonal gammopathy

Abstract: SummaryIn monoclonal gammopathies (MG) and multiple myeloma (MM), normal natural cytotoxicity receptors (NCR) expression (NCR1/NKp46, NCR2/ NKp44, NCR3/NKp30) is observed in natural killer (NK) cells. Nonetheless, except in plasma cell leukemia, few tumor plasmocytes are present in PB, while NK studies have been performed on peripheral blood (PB). For this reason we focused our attention on NK from bone marrow (BM). Our study demonstrates that the down-regulation of NCR3/NKp30 is only detectable in NK from BM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…CD160 competes with BTLA for binding to herpes virus entry mediator (HVEM) and has been shown to negatively regulate TCR-mediated signaling [26]. Crosslinking of 2B4 on T cells decreases proliferation, and 2B4 expression is upregulated on exhausted T cells [27, 28]. In our analyses both, CD160 and 2B4, were significantly upregulated on bone marrow T cells of myeloma patients suggesting that the extent of local immune suppression might be even higher than estimated from the previous investigations.…”
Section: Resultsmentioning
confidence: 99%
“…CD160 competes with BTLA for binding to herpes virus entry mediator (HVEM) and has been shown to negatively regulate TCR-mediated signaling [26]. Crosslinking of 2B4 on T cells decreases proliferation, and 2B4 expression is upregulated on exhausted T cells [27, 28]. In our analyses both, CD160 and 2B4, were significantly upregulated on bone marrow T cells of myeloma patients suggesting that the extent of local immune suppression might be even higher than estimated from the previous investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies in the BM and PB samples from patients with MGUS and symptomatic MM have shown that T lymphocytes and NK cells become quantitatively and functionally altered in the latter stage of the disease, [31][32][33][34][35][36][37][38][39][40][41][42] thereby suggesting a relation between an impaired immune system and the transformation of MM. Conversely, we 41 and others 43 have recently shown that patients in "operational cure" (ie, .10 years progression-free survival after therapy) have unique immune signatures characterized by increased numbers of effector cytotoxic CD8 1 T lymphocytes, NK cells, B lymphocytes, and normal PCs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, autologous NK cells from patients with MM appear to be dysfunctional. These NK cells can have an unfavourable balance between activating and inhibitory receptors (Fauriat et al, 2006;Costello et al, 2013) and can be inhibited by the products of plasma cells (Gherman et al, 1987) and the hypoxic bone marrow microenvironment itself (Sarkar et al, 2013). Furthermore possible protection by class I expression (Carbone et al, 2005;Gao et al, 2014) in some patients suggests that any successful activity against MM requires highly active NK cells, ideally from an allogeneic source.…”
mentioning
confidence: 99%